Bioethanol from Microalgal Biomass: A Promising Approach in Biorefinery - Silva,Carlos Eduardo de Farias (2019)
Abstract The development of new technologies which increase the production of biofuel without directly compete with food production is required. Microalgal biomass has recently been in the highlight. The role of this biomass is here discussed within the concept of biorefinery and industrial sustainability of bioethanol production. The process of cultivation in order to accumulate around 50% of carbohydrates in the biomass (dry weight) and the importance of water and nutrient recycling are reviewed. Saccharification of biomass using enzymes or acids and alternative processes such as hydrothermal liquefaction and flash hydrolysis are addressed. Since the main monosaccharide in microalgal biomass is glucose, high rates of hydrolysis and fermentation were, generally, achieved (more than 80% of the efficiency as a sum of these two processes). Anaerobic digestion to treat vinasse and the recycling of CO2 from the ethanolic fermentation and biogas could increase the process sustainability. Alternative techniques for the concentration of bioethanol from fermentation broth and for the optimization of fuel transportation are mentioned. Finally, the advantage of using microalgae rather than other sources is estimated with reference to the production rate, even though the cultivation costs are still high.